The incidence of injury among male and female intercollegiate rugby players - Peck, K. Y.; Johnston, D. A.; Owens, B. D.; Cameron, K. L. (Journal of Athletic Training, 2012)
Context: The NCAA currently classifies women`s rugby as an emerging sport. However, very few studies have examined injury rates in women`s collegiate rugby and even less have compared injury rates between female and male American players. Objective: The purpose of this study was to compare injury rates between female and male intercollegiate club rugby players at a United States Service Academy. Design: Injury surveillance data were collected and reviewed over five academic years from August 2006 through June 2011. All athletes received their care through a closed healthcare system and all injuries requiring medical attention were documented in an injury surveillance database. As a result, nearly all injuries experienced by rugby players during the study period were documented. Injury was defined as an event occurring during rugby training or competition which required attention from a medical provider. The Academy requires strict adherence to accountability; therefore, exposure data was available through roster and attendance records for all rugby participants during the study period. Setting: US Service Academy. Participants: Participants were college rugby players. There were 129 females and 240 males that participated during the five year study period. Main Outcome Measures: The primary outcome of interest was the incidence rate (IR) of injury during the study period per 1000 player-days. We calculated rate ratios (RR) using a poison distribution to compare the rates by sex. Results: During the study period there were 200 injuries documented among females (IR=2.91) and 459 injuries among males (IR=3.77). The overall incidence rate for injury was 30% higher (95% CI: 1.09, 1.54) among men when compared to women; however, the distribution of injuries varied by sex. The incidence rate for ACL injury among female rugby players was 5.3 times (95% CI: 1.33, 30.53) higher when compared to males. In contrast, males were 2.5 times (95% CI: 2.41, 2.67) more likely to sustain a fracture than females. The rate of acromioclavicular joint injury was also 2.2 times (95% CI: 1.03, 5.19) higher among males when compared to females. While the rates of concussion were similar between males and females, males were 5.3 times (95% CI: 2.22, 17.79) more likely to sustain a facial injury, 2.5 (95% CI: 0.92, 8.39) times more likely to experience an eye injury, and11.3 times (95% CI: 10.74, 11.87) more likely to sustain a head injury other than concussion. Finally, males were 6.5 times (95% CI: 2.65, 20.91) more likely to have an open wound than females. Conclusions: The results of this study illustrate some key differences in injury patterns between female and male American rugby players. These differences may reflect distinct playing styles which could be the result of the American football backgrounds which are common among many male players.